Strategic directions of restructuring of domestic corporations of oil and gas industry - Данилюк, М. О.; Фадєєва, І. Г. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Increase opportunities and potential threats to the reducing the effectiveness and competitiveness of domestic oil and gas companies were investigated. The need of its restructuring and procedure of forming a development strategy were justified. Strategic directions of restructuring of domestic vertically integrated companies, which will insure its transfer to the effective economic activity were proposed.